A Challenge and Development of Corporate Zakat Distribution on Shari'ah Commercial Banks in Nanggroe Aceh Darussalam - Ida Friatna; Chairul Fahmi; Azka Amalia Jihad (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2025)
The purpose of this study is to find out how the concept and mechanism of corporate zakat distribution in Islamic banking, as well as the challenges and obstacles in the issuance of corporate zakat with special case of Islamic Commercial Banks in Aceh. This study uses a normative sociological approach where the main data is obtained from the results of interviews and annual reports of Islamic banking in Aceh from the period 2020 to 2021. Data collection techniques through interviews and documentation data. The results showed that of the 4 Islamic Commercial Banks only Bank Muamalat Indonesia paid corporate zakat and the other 3 Banks only issued employee zakat. But the three banks in 2020 did not issue their zakat to Baitul Mal but to zakat institutions managed through foundations. One of the obstacles or causes of some Islamic Commercial Banks that do not pay zakat to Baitul Mal is that at that time covid-19 was rife, this resulted / had an impact on the bank experiencing a decrease in income or it could be said that the economy was paralyzed due to the impact of covid-19, finally the zakat management organization decreased its income. So the zakat that should have been issued by the company to Baitul Mal has been channeled to the handling of the corona virus public health center for needs during the pandemic, the aim is that the community can avoid the covid outbreak that is currently raging.